The prevention of smallpox in the eighteenth and nineteenth centuries, and the consequent demographic and economic effects - Richardson, Michael E. (The University of Edinburgh, 1968)
Through a fearful dread of the disease, preventive measures have arisen. The Chinese, the Brahmins of India, the Arabians and the Africans all knew from earliest times that the inoculation of matter from a mild case of smallpox often produced a slight form of the disease, which would protect against a severe infection. The method preferred by the Orientals was to insert smallpox crusts into the nostrils, whereby the disease was communicated through the respiratory tract. Inoculation (or variolation) was in early use in Wales and the Highlands of Scotland.

In Western Europe the medical efforts were directed not towards prevention but towards treatment. In England in the seventeenth century, and indeed well into the eighteenth, the orthodox treatment for smallpox comprised of isolation of the patient, rest in bed in a hot, ill- ventilated room, frequent blood -lettings, and overdrugging. In essence, a regime not too compatible with survival. Sydenham, who rejected this belief that the disease was contagious - for the scourge was so universal that some believed it to be congenital - proposed the "cooling method ". There were no fires allowed in the patient's room, windows were opened and bedclothes were "laid no higher than the waist ". Under this mild treatment his patients did well, but few doctors adopted it, feeling his treatment was essentially to do nothing.